OXIDATIVE CHANGES AND COGNITIVE FUNCTION DECLINE IN AGING RATS - FRANCIS RUDIN, MUHAMMAD IRFAN NORMAN; MAKPOL, SUZANA; WAN NGAH, WAN ZURINAH; MOHD YUSOF, YASMIN ANUM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims to show that impairment of cognitive function occurred during aging is related to increased oxidative stress. Methods: A total of 36 Sprague Dawley rats were divided into four groups: Young (3 months), middle (14 months), and old age groups (18 and 23 months). Rats were killed and blood was collected for the measurement of oxidative stress which includes deoxyribonucleic acid (DNA) damage and lipid peroxidation (malondialdehyde [MDA] levels). Cognitive function of rats was measured through open-field experiments, Morris water maze (MWM), and object identification. Results: Increased DNA damage and MDA levels were found in middle age and old rats compared to young rats (3 months old, p<0.05). There was an increase in anxiety with age as indicated by the increased production of fecal boli and decreased activity of grooming and rearing. For the navigation test, older rats took a long time to search for the hidden platform compared to young rats. In the probe test (spatial memory test 24 h after the last training), the middle- and old-age groups spent less time at the quadrant compared to the young age group. Conclusion: There is a decline in cognitive function with increased oxidative stress in aging rats.